ADHERENCE TO DIABETES MELLITUS TREATMENT GUIDELINES FROM THEORY TO PRACTICE: THE MISSING LINK - Hashmi, Noreen Rahat; Khan, Shahzad Ali (Journal of Ayub Medical College Abbottabad, 2016)
Diabetes mellitus is a complex multisystem disease that requires high quality care. Clinical practice guidelines help physicians and patients make the best possible health care decisions and improve health care management of diabetic patients. These guidelines provide the norms for clinical management as well as monitoring of diabetes care. They are not simple algorithms but are based on structured evidence based diabetic management protocols developed from randomized controlled trials. Despite the widespread availability of these diabetic guideline, their use is suboptimal at best. There are several factors blamed for contributing to this missing link from available theoretical guideline recommendations to practical applications of these guidelines. We present a brief review based on available literature review for an ongoing interventional study being done by authors in two tertiary care hospital in Lahore Pakistan for improving adherence to diabetes guidelines. We will discuss guideline implementation cycle and also present a framework encompassing various factors involved in adherence to guidelines. Until recently the emphasis to improve the guideline adherence targeted the factors relating to individual health care professionals in reference to their knowledge, attitude practice of the guidelines. However, we will discuss that broader range of health care systems, organizational factors, and factors relating to patients which may also significantly impact the adherence to the guidelines. The framework emphasises that it is important to understand the factors that act as barriers and contribute to the missing link between theory and practice of diabetic guidelines. This will help plan appropriate strategies in the pre-implementation stage for effective and improved diabetes guidelines adherence and management. Keywords: Diabetes mellitus; Diabetes management; Diabetic guidelines; Adherence to guidelines